India's fast reactor programme – A review and critical assessment - Kale, R.D. (Progress in nuclear energy (New series), 2020)
It is nearly fifty years since the beginning of the fast reactor development programme in India. Nuclear energy has substantial higher potential especially when fast breeder reactors are brought into play even with moderate reserves of uranium as is the case with India. While a beginning was made by setting up the Fast Breeder Test Reactor (FBTR) operating at Kalpakkam since 1985, there is an imperative need to build a robust fast reactor programme as the second stage of India's much publicised three stage nuclear power programme. This article focuses first on challenges and gains from FBTR followed by current status of the Prototype Fast Breeder Reactor, PFBR at Kalpakkam. It then elaborates on evolution of its current design, development of components, delays suffered during its commissioning, and emphasis to retain technical expertise in this totally new technology. Finally it suggests a way forward to maintain relevance of the programme by accelerating advanced fuel development with high breeding ratio. •Indian Fast Reactor programme background, Choice of sodium cooled (fast) reactor, Fast Breeder Test Reactor (FBTR), Fuel development, Gains from FBTR.•Prototype Fast Breeder Reactor (PFBR), Design evolution, Timeline of programme, Engineering data related to FBTR and PFBR, Component manufacture and testing.•Sodium circuits commissioning, Difficulties faced, Delays, Utilizing expertise of retired persons involved in FBTR and R&D.•Future challenges, Metal fuel development, Need for commissioning authority to oversee commissioning.•Planning future reactor work with advanced fuel.